Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I want to solve this system of equations, I have been out of Maths for a long!!



Just wondering easiest step to find values for $x$ and $y$ from the above equations?

share|cite|improve this question
This is one of those `awkward' questions. Equations of this form (with $a$ and $b$ replacing 7 and 11) reduce to quartics, which do have analytic solutions, but they're pretty horrible. On the other hand, these particular equations have an integral solution. – Chris Taylor Feb 13 '12 at 18:28
@ChrisTaylor (9,4) is the only one. – Pedro Tamaroff Feb 13 '12 at 18:31
Why is "slope of a line" in the title? – Américo Tavares Feb 13 '12 at 19:15
@AméricoTavares , I should have explained Derivation for x and y !! My initial hunch on deriving the above equation was based on y = mx + b !! Its my fault, – Medex Feb 13 '12 at 23:17
@Medex: I changed the title and retagged your question. – Américo Tavares Feb 14 '12 at 0:03
up vote 3 down vote accepted

Note that : $x,y \geq 0$

$(7-y)^2=11-\sqrt y$

substitute $~\sqrt y = t~$ , so :

$(7-t^2)^2=11-t \Rightarrow t^4-14 \cdot t^2+49=11-t \Rightarrow t^4-14 \cdot t^2+t+38=0$

Note that possible nonnegative integer solutions of equation $~\sqrt x+y=7~$ are :

$(x,y) \in \{(1,6),(4,5),(9,4),(16,3),(25,2),(36,1),(49,0) \}$

Since pair $(x,y)$ has to be solution of equation $\sqrt y +x =11$ also we have that :

$(x,y)=(9,4) \Rightarrow \sqrt y=2 \Rightarrow t=2 ~$

Therefore polynomial $~t^4-14 \cdot t^2+t+38~$ has to be divisible by $(t-2)$

If you divide this polynomial by $(~t-2)~$ using Polynomial long division method you will get polynomial :


So you should solve equation $~t^3+2t^2-10t-19=0~$ to obtain other solutions .

This can be done using general formula of roots .

share|cite|improve this answer
I am able to derive upto this equation t ^ 4 −14 ^ t ^ 2 +t+38=0 , from then i am lost !! Can you please explain the rest – Medex Feb 13 '12 at 22:08
I said upto this step : t 4 −14⋅t 2 +t+38=0 – Medex Feb 13 '12 at 22:10
@Medex,see edit... – pedja Feb 14 '12 at 5:03
@TPedja Great Thank you !! Your Derivation helped me a lot !! – Medex Feb 14 '12 at 17:14

There are no easy steps to solve the given system of two equations $$ \begin{eqnarray} \sqrt{x}+y &=&7 \tag{1} \\ \sqrt{y}+x &=&11, \end{eqnarray}$$ which is equivalent to $$ \begin{eqnarray*} \sqrt{x} &=&7-y \\ \sqrt{y} &=&11-x. \end{eqnarray*}$$ If you square both equations you get $$ \begin{eqnarray*} x &=&\left( 7-y\right) ^{2} \\ y &=&\left( 11-x\right) ^{2}, \end{eqnarray*}$$ whose solutions include the solutions of the given system. Now substitute the second in the first and vice-versa $$ \begin{eqnarray*} x &=&\left( 7-\left( 11-x\right) ^{2}\right) ^{2}\Leftrightarrow \left( 7-\left( 11-x\right) ^{2}\right) ^{2}-x=0 \\ y &=&\left( 11-\left( 7-y\right) ^{2}\right) ^{2}\Leftrightarrow \left( 11-\left( 7-y\right) ^{2}\right) ^{2}-y=0 \end{eqnarray*}$$ and expand the left hand sides to get two quartics $$ \begin{eqnarray} x^{4}-44x^{3}+712x^{2}-5017x+12\,996 &=&0 \tag{2} \\ y^{4}-28y^{3}+272y^{2}-1065y+1444 &=&0. \end{eqnarray} $$

Instead of solving these two equations by the standard method, we can first apply the rational root theorem, from which we know that the possible integer roots are of the form $x=\pm p,y=\pm q$, where $p$ and $q$ are integer factors of the constant terms, respectively, $ 12996=2^{2}3^{2}19^{2}$ and $1444=2^{2}19^{2}$. By direct computation we conclude that only $x=9$ and $y=4$ are integer solutions $$ \begin{eqnarray*} \sqrt{9} &=&7-4 \\ \sqrt{4}+9 &=&11. \end{eqnarray*} $$ Since $$\begin{eqnarray*}x^{4}-44x^{3}+712x^{2}-5017x+12996=\left( x-9\right) \left( x^{3}-35x^{2}+397x-1444\right) \end{eqnarray*} $$ and $$ \begin{eqnarray*}y^{4}-28y^{3}+272y^{2}-1065y+1444 =\left( y-4\right) \left( y^{3}-24y^{2}+176y-361\right) \end{eqnarray*} $$ we still need to find the roots of two cubic equations, one in $x$ and the other in $y$ $$ \begin{eqnarray} x^{3}-35x^{2}+397x-1444 &=&0 \tag{3} \\ y^{3}-24y^{2}+176y-361 &=&0. \end{eqnarray}$$

It would be possible to find the roots algebraically, but the computation is so long that I computed the roots numerically in SWP $$ \begin{eqnarray*} x &\approx &7.8687,\quad x \approx 12.848,\quad x \approx 14.283 \\ y &\approx &3.4156,\quad y \approx 9.8051,\quad y \approx 10.779. \end{eqnarray*} $$

Edited. However these solutions are not solutions of the original system. For instance, for $x\approx 7.8687$, from $\sqrt{7.868\,7}+y=7$, we find $ y\approx 4.1949$, which is not a solution of $\sqrt{y}+x=11$ $$ \sqrt{4.1949}+7.8687\approx 9.9168\neq 11, $$ and similarly for the other solutions. So the only solution is $\left( x,y\right) =\left( 9,4\right) $.

Added. Here is a plot of the two curves, $\sqrt{x}+y=7$ (blue) and $\sqrt{y}+x=11$ (black), which cross each other at $(x,y)=(9,4)$.

enter image description here

share|cite|improve this answer
Thanks for your comment, I have noticed that you have included a more detailed answer with a graph, so I will remove my previous answer. – NoChance Feb 14 '12 at 12:46
@EmmadKareem You are welcome. – Américo Tavares Feb 14 '12 at 13:40
@AméricoTavares, Great help ! You also have changed the title and made it easier !! Thank you so much !! – Medex Feb 14 '12 at 17:15
@Medex You are welcome. – Américo Tavares Feb 14 '12 at 17:20

First rearrange the equations like this: $$y-4=3-\sqrt{x} \\x-9=2-\sqrt{y}$$ then multiply two sides of these equations to each other; $$(y-4)(x-9)=(3-\sqrt{x})(2-\sqrt{y})$$ Since $x,y\ge 0$ we can factor LHS : $$(\sqrt{y}-2)(\sqrt{y}+2)(\sqrt{x}-3)(\sqrt{x}+3)=(3-\sqrt{x})(2-\sqrt{y})$$ Implies that$$ (\sqrt{y}-2)(\sqrt{x}-3)((\sqrt{y}+2)(\sqrt{x}+3)-1)=0 $$ at least one of the factors must be zero.

1. $$(\sqrt{y}-2)=0 \Rightarrow y=4$$

by substitution $y=4$ in the first eq. we have $x=9$.

and by checking in the second eq. implies that $$x=9\qquad and \qquad y=4$$ is a solution.


2. $$(\sqrt{x}-3)=0 \Rightarrow x=9$$

by substitution in the first eq. we have $y=4$ and by checking in the second eq. implies that this is not a new solution.


3. $$(\sqrt{y}+2)(\sqrt{x}+3)-1=0 \Rightarrow (\sqrt{y}+2)(\sqrt{x}+3)=1$$ but it has no solution for $x$ and $y$ because $$ (\sqrt{y}+2)\ge 2 ; \quad (\sqrt{x}+3) \ge 3 \Rightarrow (\sqrt{y}+2)(\sqrt{x}+3)\ge 6 $$ as a result $(\sqrt{y}+2)(\sqrt{x}+3)=1$ has no solution for $x$ and $y$.

share|cite|improve this answer

I'll solve a related system of equations: $$A + B^2 = 7$$ and $$B +A^2=11$$

Solving for $A$ in the first gives $$A=7-B^2$$ Substituting this into the second equation gives $$B+(7-B^2)^2 = 11$$ from which we arrive at $$B^4 -14B^2+B+38=0$$

Added Here, my goal is to find some solution(s) to this quartic (i.e. fourth degree) equation. There is a theoretical result that tells us what the rational (this includes integers) solutions will be, if there are any.

Basically, the rational root theorem says that in this case, any rational root will divide $38$.

We (the royal we ... I) then employ a technique known as synthetic (polynomial) division. I will not go into much detail, except to mention that I usually test smaller potential roots first... so testing $\pm 1, \pm 2 $ gives us that $B = 2$ is a solution. When we have exhausted our potential rational roots, we see that this is the only rational solution.

It then follows that $A=3$, since if $B = 2$, the first equation can be rewritten as $$A + 2^2 = 7$$

share|cite|improve this answer
Rationality of solutions is not an issue here. The solution $(9,4)$ has already been identified. It remains to prove that there are no other solutions. – Christian Blatter Feb 13 '12 at 20:21
@Christian: the OP asked for steps in determining solutions. While you might not accept my solution of a related problem, neither do I accept an identification of a solution when a student has asked for a method. – The Chaz 2.0 Feb 13 '12 at 21:16
@TheChaz , I am able to understand your last part of the derivation .. B4−14B2+B+38=0 , From then can you please explain me how you are able to generate B=2 and A=3 – Medex Feb 13 '12 at 23:09
@TheChaz Great Thank you !! Your Derivation was simple and easy to follow !! Thank you for your help !! – Medex Feb 14 '12 at 17:13

The OP asked for the "easiest steps" to solve this system of equations. Here is what I would do:

Given that the occurring expressions are so simple I would try to get a global overview by drawing a figure. This means that we have to intersect the two graphs $$y=7-\sqrt{x}\quad(x\geq0)\ ,\qquad y=(11-x)^2\quad(x\leq11)$$ (note restriction of $x$ for the second graph!). Looking at the figure one immediately sees that there is exactly one intersection point; one guesses that this is the point $(9,4)$. Plugging this point into the original system of equations one verifies that it is indeed a solution.

In order to prove that we were not cheated by our eyes we have to prove that the auxiliary function $$f(x)\ :=\ (11-x)^2-(7-\sqrt{x})=114-22x+x^2+\sqrt{x}$$ has exactly one zero in the interval $[0,11]$. Unfortunately the derivative $$f'(x)=-22+2x+{1\over 2\sqrt{x}}$$ is not strictly negative in this interval; so we have to take some extra measures: When $0\leq x\leq5$ then $f(x)\geq 114-22x\geq4$, and when $10\leq x\leq11$ then $f(x)\leq 1-7+\sqrt{x} < -2$. For the intermediate interval $[5,10]$ we now can show that $f$ is strictly decreasing: $$f'(x)\leq -22+20+{1\over 2\sqrt{5}} < -1\ .$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.